The Indonesian-English Code-Mixing in Just Alvin Show at Metro TV - Enggar Mulyajati (Universitas Bunda Mulia, 2018)
Globalization requires Indonesian people to master international language, English. At first Indonesian bilingual speakers speak vernacular and Indonesian language yet nowadays they speak Indonesian language and English. The use of English occurs not only in formal situation but also informal situation. Bilingual speakers used to mix their English to Indonesia language in informal conversation, which is called code-mixing. The symptom of code-mixing in informal situation is found in Just Alvin talkshow at Metro TV. This research is aimed at discovering the types of code-mixing and syntactic units are mixed in the speeches. The data of this qualitative research is conversation transcriptions. The result shows that there are three types of code-mixing and three syntactic units found. The types of code-mixing are insertion, alternation, and congruent lexicalization. While the syntactic units mixed in the conversation involve words, phrases, and clauses. Keywords: bilingualism, code-mixing, Just Alvin